Cruelty as Citizenship : How Migrant Suffering Sustains White Democracy - Beltrán, Cristina (Forerunners (Minneapolis, Minn.), 2020)
Why are immigrants from Mexico and Latin America such an affectively charged population for political conservatives? More than a decade before the election of Donald Trump, vitriolic and dehumanizing rhetoric against migrants was already part of the national conversation. Situating the contemporary debate on immigration within America's history of indigenous dispossession, chattel slavery, the Mexican-American War, and Jim Crow, Cristina Beltrán reveals white supremacy to be white democracy--a participatory practice of racial violence, domination, and exclusion that gave white citizens the right to both wield and exceed the law. Still, Beltrán sees cause for hope in growing movements for migrant and racial justice. Forerunners is a thought-in-process series of breakthrough digital works. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship.